2010
DOI: 10.1021/jo1010763
|View full text |Cite
|
Sign up to set email alerts
|

Oligonucleotide Incorporation and Base Pair Stability of 9-Deaza-2′-deoxyguanosine, an Analogue of 8-Oxo-2′-deoxyguanosine

Abstract: 9-Deaza-2'-deoxyguanosine (CdG) is a C-nucleoside and an analogue of the abundant promutagen 8-oxo-2'-deoxyguanosine (OdG). Like 2'-deoxyguanosine (dG), CdG should form a stable base pair with dC, but similar to OdG, CdG contains an N7-hydrogen that should allow it to also form a relatively stable base pair with dA. In order to further investigate the base pairing of CdG, it was incorporated into DNA and paired with either dC or dA. Melting studies revealed CdG:dC base pairs are less stable than dG:dC base pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 45 publications
2
25
0
Order By: Relevance
“…8-oxo-dG residues have been reported to destabilize ASO:DNA duplexes [ 27 , 29 , 30 ]. However, ASOs are generally used to target RNA rather than DNA molecules.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…8-oxo-dG residues have been reported to destabilize ASO:DNA duplexes [ 27 , 29 , 30 ]. However, ASOs are generally used to target RNA rather than DNA molecules.…”
Section: Resultsmentioning
confidence: 99%
“…It was hypothesized that the antisense activity of oligonucleotides containing 8-oxo-dG may be increased due to the ability of corresponding nucleobases to acquire tautomeric forms, which enables enhanced binding to complementary normal nucleobases [ 33 ]. However, experimental data revealed that the incorporation of 8-oxo-dG residues reduced the Tm of ASO:DNA and ASO:RNA duplexes (Figs 1 , 5A and 5B ), probably because the major tautomer of 8-oxo-dG in aqueous solution is the 6,8-diketo form [ 64 ], which binds to complementary dC residues more weakly than does the standard dG residue [ 29 ]. Thus, the contribution of the strongly binding minor zwitterionic tautomer of 8-oxo-dG ( Fig 1A ) may be too small to be detected.…”
Section: Discussionmentioning
confidence: 99%
“…Both de Oliveira and Gao left the consortium and Clifford Padgett ( Armstrong Atlantic State University , biochemistry) and Adam Van Wynsberghe ( Hamilton , biochemistry) were invited into the consortium in the second year of the grant. MERCURY faculty published 62 publications during the third MRI grant period, [ 97–158 ] that is, an average of 1.7 papers published per investigator per year, a rate 3.4 times the average rate at PUIs. [ 46 ] The Shields lab's papers on water clusters have been cited over 150 and 190 times, [ 131,143 ] and their review article on p K a calculations has been cited over 130 times.…”
Section: Research Accomplishments (Intellectual Merit) and Transformamentioning
confidence: 99%
“…This allows these compounds to engage in alternative hydrogen-bonding patterns such as Hoogsteen base pairing, which may find use in complex oligonucleotide structures or in the investigation of polymerases. 1115 Similarly, Hamm et al have evaluated alternate hydrogen-bonding patterns for 2′-deoxy-9-deazaguanosine to study the promutagenic characteristics of 8-oxo-2′-deoxyguanosine. 15 …”
mentioning
confidence: 99%
“…1115 Similarly, Hamm et al have evaluated alternate hydrogen-bonding patterns for 2′-deoxy-9-deazaguanosine to study the promutagenic characteristics of 8-oxo-2′-deoxyguanosine. 15 …”
mentioning
confidence: 99%